Blissfully yours (2002) - Apichatpong Weerasethakul ([United Kingdom] : Second Run DVD, 2006)
Special features: introduction to the film by the director, booklet with essay, cast bios, production notes and photos.
Thai and Burmese spoken, English subtitles
Onderzoek KASK Professioneel (OFVP)
film
Keywords: Apichatpong Weerasethakul